Profiling Cognition and Speech in Individuals With Parkinson's Disease Seeking Speech Therapy - Jean Marie Priscott; Cristina Pino; Elizabeth Schoen Simmons; Rui Liu; Ciara Leydon (Perspectives of the ASHA Special Interest Groups, 2026)
Purpose: The primary objective of this study was to develop a preliminary cognitive profile of people with Parkinson's disease (PWPD) and dysphonia seeking speech therapy. The secondary objective was to compare voice deficits among individuals with Parkinson's disease (PD)-related dysphonia with and without cognitive impairments. Method: The cognitive profile of 10 male and five female PWPD, aged 54–77 years, was assessed using Level I (screening) and Level II (comprehensive battery of neuropsychological tests) testing. Participants were grouped as cognitively intact (PD with nonimpaired cognition [PD-NC]) or cognitively impaired (PD with impaired cognition [PD-IC]) according to their testing performance in Level II testing. Acoustic and self-reported vocal handicap measures were compared across participants classified as having PD-NC or PD-IC. Results: Of the 15 participants who enrolled in this study, six (40%) were classified as having PD-IC using Level I testing, compared with nine (60%) using Level II testing. Participants classified as having PD-IC (established using Level II criteria) reported significantly higher Voice Handicap Index scores, compared with participants classified as having PD-NC. No significant differences in acoustic measures of voice quality (cepstral peak prominence, Cepstral Spectral Index of Dysphonia) and pitch variability were observed across groups. Conclusions: More than half of the participants presented with a cognitive impairment, regardless of testing level. Two cognitive domains emerged as the most consistently impaired: executive function and visuospatial skills. Participants in the PD-IC group reported worse voice-related handicap scores relative to participants in the PD-NC group; however, no significant difference in acoustic measures was observed between groups. Given the prevalence of cognitive impairments and group differences in the self-evaluation of voice disorders, consideration of cognition, in addition to speech measures, can contribute to the development of an effective treatment plan for individuals seeking speech therapy.